PENGARUH FAKTOR EKONOMI, SOSIAL, DAN DEMOGRAFI TERHADAP PENDAPATAN DAN REMITAN YANG DIKIRIM KE DAERAH ASAL OLEH MIGRAN NON PERMANEN DI KECAMATAN DENPASAR BARAT - Purwanto, Komang Arya; Sudibia, I Ketut; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.09.TAHUN 2016, 2016)
Economic activity in the province of Bali and Denpasar especially generally relies on the tourism sector. Denpasar City is one of the main destinations of migrants in the province of Bali. This is caused by the construction is done tends to converge to this area, which is reflected by the concentration of the various activities that act as a center of government, economy and trade, educational activities, health services, and tourism activities. This study aims to analyze; 1) the influence of age, sex, marital status, education, and work experience on the income of migrant workers nonpermanen 2) the influence of age, sex, marital status, education, work experience and income towards remittances by migrant workers nonpermanen to the area of ??origin, 3 ) the indirect effect of age, gender, marital status, education, and work experience to remittances by migrant workers nonpermanen through the income of migrant workers nonpermanent, 4) income mediate against age, sex, marital status, education, and work experience of the delivery remittance nonpermanen by migrant workers to their home area in West Denpasar District.
Keywords: non-permanent migrants, age, education, income, remittances